SEXUALIDADE: UMA PROPOSTA DE SEQUÊNCIA DIDÁTICA PROTAGONIZADA PELOS ESTUDANTES - Fontoura, Leticia Bonela (2020)
Human sexuality comprises not only genital sex, but also social, political, religious, ethical, cultural, and historical factors, making it universal and, at the same time, unique for each individual. In this way, the school environment is inevitably perm